1999
DOI: 10.1080/026520399283876
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure estimates of 30 elements from the UK Total Diet Study

Abstract: Dietary exposures of consumers to 30 elements (aluminium, antimony, arsenic, barium, bismuth, boron, cadmium, calcium, chromium, cobalt, copper, germanium, gold, iridium, iron, lead, lithium, manganese, mercury, molybdenum, nickel, palladium, platinum, rhodium, ruthenium, selenium, strontium, thallium, tin and zinc) estimated from the UK 1994 Total Diet Study are reported, and compared with those from previous UK Total Diet Studies and those from other countries. Dietary exposure estimates were generally low a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
142
15
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(193 citation statements)
references
References 14 publications
31
142
15
5
Order By: Relevance
“…(33.5 % of TWI), in accordance with the established PTWI percentages for total diet studies (1.6-36 %, Lee et al, 2006;Nasreddine et al, 2006;Larsen et al, 2002;Ysart et al, 1999;Urieta, Jalon, & Eguileor, 1996;Becker, & Kumpulainen, 1991) which considered that the largest source of mercury contamination lies in fish and shellfish.…”
Section: Estimated Dietary Intake Of Mercury and Arsenicmentioning
confidence: 93%
“…(33.5 % of TWI), in accordance with the established PTWI percentages for total diet studies (1.6-36 %, Lee et al, 2006;Nasreddine et al, 2006;Larsen et al, 2002;Ysart et al, 1999;Urieta, Jalon, & Eguileor, 1996;Becker, & Kumpulainen, 1991) which considered that the largest source of mercury contamination lies in fish and shellfish.…”
Section: Estimated Dietary Intake Of Mercury and Arsenicmentioning
confidence: 93%
“…Considering the high number of celiac, these information are urgently required so that the daily dietary element intakes in the celiac population can be estimated from available food consumption data. While element intake levels for non-celiac people are documented [12][13][14][15] there is as yet no information available for celiac ones. Also, this study wants to investigate if any toxic elements could be found in the gluten-free foods and the daily intake from diets composed according to reference intake levels.…”
Section: Introductionmentioning
confidence: 99%
“…Fish contains the highest level of Se, although other foods also contain Se (Ysart et al, 1999;Leblanc et al, 2005). In this study, the correlations between As and Hg and As and Se are relatively robust, whereas the correlation between Hg and Se is much weaker.…”
Section: Discussionmentioning
confidence: 49%
“…Fish and shellfish are also the major sources of As from food (Ysart et al, 1999;Leblanc et al, 2005). Fish contains the highest level of Se, although other foods also contain Se (Ysart et al, 1999;Leblanc et al, 2005).…”
Section: Discussionmentioning
confidence: 99%